In vitro biocompatibility of ICON® and TEGDMA on human dental pulp stem cells. Issue 8 (August 2016) - Gölz, Lina; Simonis, Ruth Andrea; Reichelt, Joana; Stark, Helmut; Frentzen, Matthias; Allam, Jean-Pierre; Probstmeier, Rainer; Winter, Jochen; Kraus, Dominik
Abstract: Objectives: Resin infiltrants have been successfully used in dental medicine preventing the progression of tooth decay in an early phase of caries development. ICON ® is an infiltrant of low-viscosity which penetrates via dentinal tubules into the lesion in dependence of the demineralization depth. Hence, we performed an in vitro study to determine the effect of ICON ® on human dental pulp stem cells (hDPSCs). Methods: Using explant technique, primary hDPSCs were collected from extracted teeth. Characterization and isolation were performed with typical mesenchymal stem cell markers (Stro-1, CD73, CD90, CD105) and hDPSCs differentiation was validated by immunofluorescence and flow cytometry. HDPSCs were stimulated with light-cured ICON ® (lc) and non-light-cured ICON ® (nc) conditioned media as well as different TEGDMA concentrations followed by the analysis of cytotoxicity, pro- and anti-inflammatory responses and differentiation using XTT assay, RT-PCR and ELISAs, respectively. Results: Initial analysis demonstrated that hDPSCs express characteristic mesenchymal stem cell markers and differentiate into adipocytes, chondrocytes and osteoblasts. Notably, ICON ® nc dramatically reduced cell viability (up to 98.9% after 48 h), whereas ICON ® lc showed only a modest cytotoxicity (10%). Data were in line with cytokine expression demonstrating increased levels of IL-6 and IL-8 as well as decreased IL-10 after ICON ® nc exposure compared to ICON ® lc. ICON ® lc caused almost no alterations of DSPP, whereas ICON ® nc markedly elevated DSPP mRNA levels (130.3-times). A concentration-dependent effect was observed in TEGDMA challenged hDPSCs. Significance: ICON ® is a successful minimal invasive technique. However, clinicians should strictly follow manufacturer's instructions to prevent adverse effects.